解析海峡华人领袖如何通过早期的《海峡华人杂志》塑造海峡华人独特与中间人的形象，并探讨其中的意义 = An analysis of how the Straits Chinese leaders shaped a distinct and intermediary image of Straits Chinese through the early Straits Chinese magazine and discuss its significance - 朱碧瑜 Zhu, Bi Yu (Nanyang Technological University, 2023)
19世纪末至20世纪初，海峡华人正处于重要的转折期，他们必须在社会与思想上与时并进，舍弃落后的思想、破除旧习恶俗并迎接科学知识与新文明。因此，海峡华人领袖通过创立《海峡华人杂志》（The Straits Chinese Magazine）的平台进行社会与教育的改革。此杂志汇聚了该时期海峡华人社会的思想并记载了这一关键的历史进程。本篇论文将以海峡华人为研究对象，从海峡华人的视角出发去研究海峡华人，给予他们全新的诠释。本文将逐步解析海峡华人领袖如何通过早期的《海峡华人杂志》有意识地塑造自身族群的独特与中间人形象。同时，本文将结合时代背景去探讨形象塑造的动机与意义，并论证塑造的形象是海峡华人领袖基于现实的政治考量与政治需求而着重强调的，最终的目的是为海峡华人族群争取利益。 关键词： 海峡华人、海峡华人领袖、海峡华人杂志、政治考量 In the late 19th to early 20th century, the Straits Chinese were at a crucial turning point. They needed to progress socially and intellectually, in which they had to discard their outdated beliefs and customs, and turned to embrace knowledge from the modern civilization. Therefore, the Straits Chinese leaders initiated social and educational reforms through the platform of "The Straits Chinese Magazine” where the thoughts of the Straits Chinese during this crucial historical era were reflected and consolidated. This paper focuses on the Straits Chinese and aims to provide a fresh interpretation of them through their own perspectives. This paper analyses how the Straits Chinese leaders consciously shaped the distinct and intermediary images of Straits Chinese through the early issues of "The Straits Chinese Magazine." This paper will explore the motivations and significance of this image formation by putting it in historical context. The paper argues that the image formation was purposefully emphasized by the Straits Chinese leaders to fulfil their political needs, and their ultimate goal was to advocate for the interests of the Straits Chinese community. Keywords: Straits Chinese; Straits Chinese leaders; Straits Chinese Magazine; Politics